2002
DOI: 10.1055/s-0037-1613197
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Inhibits Lipopolysaccharide-Induced Tumor Necrosis Factor-α Production by Inhibiting Activation of both Nuclear Factor-κB and Activator Protein-1 in Human Monocytes

Abstract: SummaryActivated protein C (APC), an important natural anticoagulant, inhibits tumor necrosis factor-α (TNF-α) production and attenuates various deleterious events induced by lipopolysaccharide (LPS), contributing thereby to a significant reduction of mortality in patients with severe sepsis. In this study, we investigated the mechanism(s) by which APC inhibits TNF-α production by LPS-stimulated human monocytes in vitro. Although APC inhibited LPS-induced TNF-α production in a concentration-dependent fashion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(109 citation statements)
references
References 40 publications
4
103
0
2
Order By: Relevance
“…Furthermore, recent reports demonstrate that recombinant activated protein C can induce a cell signaling response via ERK activation through a PAR-1/S1P1-dependent, but EPCR-independent, mechanism (50). Other studies have shown that blocking the binding of activated protein C to EPCR did not affect the inhibition of TNF-␣ production by activated protein C in LPS-stimulated human monocytes (11). It is also possible that there may be an alternative activated protein C-binding receptor on the surface of monocytes (51).…”
Section: Figurementioning
confidence: 97%
“…Furthermore, recent reports demonstrate that recombinant activated protein C can induce a cell signaling response via ERK activation through a PAR-1/S1P1-dependent, but EPCR-independent, mechanism (50). Other studies have shown that blocking the binding of activated protein C to EPCR did not affect the inhibition of TNF-␣ production by activated protein C in LPS-stimulated human monocytes (11). It is also possible that there may be an alternative activated protein C-binding receptor on the surface of monocytes (51).…”
Section: Figurementioning
confidence: 97%
“…sepsis receiving recombinant activated protein C contained reduced levels of IL-6 (4). In vitro studies have also revealed that 360 nM and 3.6 M activated protein C inhibited TNF-␣ secretion by CD14 ϩ peripheral monocytes and by THP-1 cells, respectively (14,15). However, the regulated secretion of numerous other cytokines by activated protein C-treated monocytes has not been documented to date.…”
Section: Figurementioning
confidence: 99%
“…More recently, activated protein C has been shown to inhibit inflammation (13)(14)(15)(16)(17)(18), apoptosis (19 -22), and to prevent increases in vascular permeability (23,24). With respect to its antiinflammatory properties, activated protein C has been shown to down-regulate the production of TNF by monocytes (13)(14)(15) and to suppress expression of leukocyte adhesion molecules in endothelial cells (16), presumably by inhibiting NF-B nuclear translocation (14) and/or down-regulating the transcription of NF-B subunits (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…in the WNC group could be the consequence of an acute phase response induced by the infectious stimulus. This response could be favourable for the host, considering its anti-inflammatory properties, as reported by Yuksel et al (2002). However, no significant differences in the levels of PC were observed in the animals that received L. casei.…”
Section: Discussionmentioning
confidence: 61%